PENGARUH IMPLEMENTASI TRANAKSI NON TUNAI, AKUNTABILITAS, DAN KEBIJAKAN LEGAL SISTEM INFORMASI TERHADAP PENGELOAAN KEUANGAN DAERAH (Studi Pada OPD di lingkungan Pemerintahan Kabupaten Barito Selatan) - Norhadijah Norhadijah; Sri Yuni; Ferry Christian (Universitas Palangka Raya, 2022)
The study is aimed at recognizing the impact of implementation of non-cash transactions, accountability and legal policies of regional financial management information systems on regional financial management in the district of barito. It is a quantitative study, that is, by the presentation of research with Numbers that are then explained and interpreted in a description to test hypotheses. The data used in this study is the primary data gleaned from the responders filling out questionnaires. Tools used in the study use descriptive and linear regression statistics. Based on analysis, it is known that :1) implementation of non-cash transactions has a positive and significant impact on financial management in the opd in south Barito county's environment 2) accountability has a positive and significant impact on the regional finance management of the opd in the south Barito government's environment. 3) the legal policies of the region's financial management system affect the management of blood money on the opd in the south of Barito county's administration.4) simultaneously implementation of non-cash transactions, accountability and legal policies of the region's financial management systems are both positive and significant to the management of regional finances in the area of Barito Selatan